Leadership and power : ethical explorations - Chakraborty, S. K.; Bhattacharya, Pradip, 1947- (New Delhi ; New York : Oxford University Press, 2001)
Contributed articles.
Includes bibliographical references and index.
Keywords: Power (Social sciences); Leadership; Social participation -- India